Environmental lithium exposure in the north of Chile - Tissue exposure indices - Leonardo T. Figueroa; Sara Ann Barton; William J. Schull; Allan H. Young; Yumi M. Kamiya; John A. Hoskins; Edward B. Ilgren (Epidemiology, Biostatistics and Public Health)
Background: northern Chile has the highest levels of lithium in surface waters in the world which is reflected in very high lithium levels in the plants and animals that depend on these water systems and consequently in the indigenous population. Methods: the lithium tissue burdens in populations from two valleys in the extreme north of Chile have been studied. The bulk of this report is based on analyses of lithium levels in urine, hair, and breast milk in the population of several villages. Data on serum levels, some of which had been previously published, are included for the sake of completeness. Since this paper reports studies by several groups of workers samples were analysed by a variety of methods. These include atomic emission, atomic absorption, other photospectroscopic techniques and mass spectroscopy. Results: in all samples studied the average lithium level (5.3 ppm) was found to be significantly elevated compared to levels reported in the literature and measured in this study for people not exposed to high levels in water and food (0.009-0.228 ppm). Conclusions: the people studied represent a unique longitudinal cohort. The work should provide important insights into the potential neuroprotective effects of lithium also help us set guidelines to assess the risks from high dose environmental exposure.